Development of a nomogram for membranous nephropathy prediction in patients with primary Sjögren’s syndrome: a 6-year retrospective study - Guo, Lihui; Zhao, Shan; Liu, Xudong (Frontiers in Immunology, 2024)
Objectives: Nephritis is a life-threatening complication of primary Sjögren's Syndrome (pSS), with membranous nephropathy (MN) being prevalent. Renal biopsy is the gold standard for MN diagnosis, but it is invasive and cannot be repeatedly performed. This study aimed to develop a nomogram for the prediction of MN in patients with pSS.Methods: This retrospective study included patients with pSS admitted to the Rheumatology and Immunology Department of the First Affiliated Hospital of China Medical University between January 2015 and January 2021. A nomogram was developed using multivariable logistic regression analysis and evaluated using receiver operating characteristic (ROC) curve analysis. Bootstrap resampling analysis (1000 times) was performed to evaluate the nomogram for discrimination and the calibration curve for consistency.Results: A total of 237 patients with pSS [aged 53.00 (44.00, 61.00) years] were included, with 35 pSS-MN patients. Based on clinical practice and multivariable logistic regression analysis, seven variables associated with pSS-MN were selected, including white blood cells, creatine, complement 3, rheumatoid factor, antinuclear antibodies, anti-SSA antibody, and interstitial lung disease. The area under the ROC curve was 0.860 (95% confidence interval: 0.796-0.919), indicating good predictive power. In addition, the nomogram exhibited excellent performance, as demonstrated by the calibration curve and decision curve analysis.This study developed a risk prediction nomogram for MN in patients with pSS, with high predictive power. It may be used to improve the management of patients with pSS.